Improving Writing Skills in ELT Classrooms: Insights from Action Research - Bhatt, Deepak Raj (Journal of Research in Education, 2025)
Writing is the most important skill for English language learners. It demands not only the grammatical accuracy but also the coherence, cohesion, organization, creativity and originality. This exploratory action research explored the strategies to uplift students’ writing skill in the English Language Teaching (ELT) classroom. The study was carried out in 34 students of grade 8. The study strictly followed a framework of exploration, planning, action, observation, and reflection. The implementation included guided writing practices, peer review works, the use of clues, and collaborative learning strategies. The researcher collected data through open and close-ended questionnaires, samples of students’ written work, classroom observation records, and reflective journals of the teachers.The result stated that students faced difficulties in generating and organizing ideas, choosing appropriate vocabulary and structures, and organizing it to their writing. Collaborative practices in the classroom increased students’ engagement and encouraged them to have fun along with writing. Teacher feedback greatly supported them to improve their accuracy and clarity. The research explores that using process-oriented techniques with supportive classroom practices creates and strengthens a more productive environment for developing writing skills on the part of learners. The study summarizes that exploratory action research provides teachers with a valuable input for modifying methods according to learners’ needs improving both linguistic proficiency and learner autonomy in the ELT classroom.